1995
DOI: 10.1017/s0079497x00003030
|View full text |Cite
|
Sign up to set email alerts
|

Coygan Cave, Laugharne, South Wales, a Mousterian Site and Hyaena Den: a Report on the University of Cambridge Excavations

Abstract: Excavation by Charles McBurney and John Clegg during the early 1960s revealed a sequence with a Mousterian occupation, of which the principal finds were two bout coupé handaxes, stratified close to the base of a Middle Devensian hyaena-den accumulation. The human occupation should belong within the period 64–38 ka with comparative and stratigraphic evidence favouring a date within the earlier part of this range before 50 ka. The hyaena-den occupation probably extends from at least 40 ka (if not 60 ka) until c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…12A), which would at first appear to exclude the possibility of the bone accumulation being due a human activity, since humans usually hunted non-herbivorous during the Middle Palaeolithic and generally only a few percent of the bones at their camp sites are from carnivores (Aldhouse-Green et al, 1995;Fosse et al, 1998;Pickering, 2002;Lansing et al, 2007;Kuhn et al, 2008). The remains of these large carnivores at Westeregeln are dominated by hyena remains (Fig.…”
Section: Hyena Versus Human Prey-bone Accumulations and Bone Taphonomymentioning
confidence: 98%
See 1 more Smart Citation
“…12A), which would at first appear to exclude the possibility of the bone accumulation being due a human activity, since humans usually hunted non-herbivorous during the Middle Palaeolithic and generally only a few percent of the bones at their camp sites are from carnivores (Aldhouse-Green et al, 1995;Fosse et al, 1998;Pickering, 2002;Lansing et al, 2007;Kuhn et al, 2008). The remains of these large carnivores at Westeregeln are dominated by hyena remains (Fig.…”
Section: Hyena Versus Human Prey-bone Accumulations and Bone Taphonomymentioning
confidence: 98%
“…Pickering, 2002;Kuhn et al, 2008), and especially from those left at Middle Palaeolithic sites. Few contemporary used hyena and Neanderthal sites have been described from the open air and cave sites of England and northern Germany, or in the mammoth steppe environment and adjacent cave-rich regions of north-central Europe, in England and northern Germany (Aldhouse-Green et al, 1995;Diedrich, 2010aDiedrich, , 2011d.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons many of the samples which we have dated are bones and teeth of animals without evidence of direct human associations and it is their contexts which make them helpful. Indeed, several of the samples are teeth of hyaenas and it is entirely hyaena teeth which, because of the clarity of their relative stratigraphy, have been selected as samples in an ongoing investigation of the age of handaxes from Coygan Cave near Laugharne in Carmarthenshire (Aldhouse-Green et al, 1995). Jö ris and colleagues (2003) suggest that charcoal is to be preferred to bone as a dating material for the Palaeolithic because bone sometimes gives ages that are too young, although others have found that this is by no means consistent in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…Fosse 1997). Outside the study region, reindeer is relatively common in some hyena assemblages (Srbsko-Chlum-Komin, 15% of NISP), Hostim-Nad Kacakem (15%), Tetin-Turska Mastal (10%), Koneprusy caves (Prosek dome) (7%), all Czech Republic (Diedrich and Žák 2006), Coygan Cave, Wales (9%; Aldhouse-Green et al 1995), yet rare in others that were definitely accumulated during cold conditions (e.g. Morancourt, France (2.8% of NISP), Fouvent, France (absent, Fosse 1997), dated to Châtelperronian), Tman-Axamitova Brana (3%), Praha-Hlubocepy-Svatoprokopska (1%), both Czech Republic (Diedrich and Žák 2006), Veldwezelt, Belgium (0.8%;Bringmans 2006).…”
Section: Middle Palaeolithic Archaeozoologymentioning
confidence: 99%